How resilient is the activity-based cost system? / Wee Shu Hui - Wee, Shu Hui
The whole issue of cost allocation or absorption has always generated a lot of interest amongst accountants probably because no absoluteness of costs has emerged as yet. Would “true” costs ever surface? Historically, textbooks have emphasised methods for allocating costs to departments and products. Fixed costs have been divided by some standard measure to obtain a fixed cost unit (even though fixed costs are supposed to be “fixed”). Joint costs and other common costs have been allocated by some forms of reasonable but arbitrary measures. Miller and Vollmann (1985) have identified “overhead creep” in this present age of high technology. Previously, the ratios of overhead costs to direct labour costs were 100% to 200% or so but now the rates can well escalate to over 1000%. This arises because a small change in labour can cause a substantial change in the expected overhead. Miller and Vollmann (1985) stressed the need to understand and manage costs in the “hidden factory” rather than just knowing the mechanics of allocating overhead.